The intranet management handbook - White, Martin S. (Martin Scott), 1948- (Medford, N.J. : Information Today, 2011)
"Offers a wealth of practical advice on intranet management, based on the work of the author as an intranet consultant over the past fifteen years"--Provided by publisher.
Managing intranets : opportunities and challenges -- Defining user requirements -- Making a business case -- Developing a content strategy -- Enhancing collaboration -- Managing technology -- Specifying and selecting software -- Using Microsoft SharePoint for intranets -- Establishing the intranet team -- Managing intranet projects -- Evaluating risks -- Conforming to compliance requirements -- Enhancing the user experience -- Marketing the intranet -- Measuring user satisfaction -- Creating the governance framework -- Developing an intranet strategy -- From intranets to information management.
Includes bibliographical references and index.
Keywords: Intranets (Computer networks) -- Management